Corynebacterium endocarditis of a percutaneously placed transcatheter pulmonary valve. (8th October 2013) - Johnson, Jason N.; Miller, Stephen G.; Lodge, Andrew J.
Abstract We report a case of endocarditis of a transcatheter pulmonary valve-in-valve in a 14-year-old boy with tetralogy of Fallot. He presented with recurrent low-grade fevers, lethargy, and anorexia. Multiple blood cultures grew a gram-positive rod, Corynebacterium pseudodiphtheriticum. He was taken to the operating room for removal of the vegetative endocarditis and pulmonary valve replacement.